Assessment of preoperative and postoperative anxiety in adults during extraction of impacted third permanent molars - Selimović Edin; Bajrić Elmedin (Balkan Stomatological Society, 2023)
Background: Dental fear and anxiety (DFA) is ubiquitous among the adult population. The anxiety component of DFA is more strongly expressed in adults, and includes a physiological and psychological component, and is more often analyzed in research. Oral-surgical interventions represent a significant source of stress for the appearance of anxiety in subjects. The research aim was to analyze the presence of anxiety with the use of the revised Corah Dental Anxiety Scale (DASR) and the Spielberger State Trait Anxiety Inventory (STAI) in adult patients during the treatment of extraction of impacted third permanent molars by oral surgery. Material and Methods: The study included adult patients of both sexes, who were previously scheduled for oral-surgical removal of third permanent molars. Anxiety levels were assessed preoperatively and postoperatively as follows: 1st measurement (day of examination)-DASR, and STAI (X1 and X2); 2nd measurement (immediately before the intervention)-STAI (X1 and X2); 3rd measurement (day after the intervention)-STAI (X1 and X2). Results: Preoperatively, the presence of high levels of general anxiety, situational anxiety, and dental anxiety was determined. The levels were decreased before the planned surgery and were significantly reduced in the postoperative period. The STAI scale could be used to assess the presence of situational anxiety in the dental office on an equal footing with other known measuring instruments (e.g. DASR). Conclusions: Adequate therapy should be considered to prevent preoperative anxiety, which would increase the satisfaction of patients and therapists while reducing complications related to this type of intervention.